Sport nutrition and doping factors in swimming; Parallel analysis among athletes and coaches - Sajber, D.; Rodek, J.; Escalante, Y.; Olujic, D.; Sekulic, D. (Collegium Antropologicum, 2013)
The sport nutrition and doping are known to be important issues in sports, but there is evident lack of studies which investigated those issues in swimming, especially with regard to parallel analysis of coaches and athletes. The first aim of this study was to compare knowledge of swimming coaches and their athletes about nutrition and doping. Also, we have identified interrelationships between studied sociodemographic-, sport-; nutrition- and doping-related-factors. The sample of subjects comprised 55 athletes (20.3±2.2 years of age; 24 females) and 22 coaches (mean age 36.5±7.8 years; 4 females) from Croatia (98% of respondents). In the first phase of the investigation we have validated specific questionnaires to determine the knowledge of sport nutrition (KSN), and knowledge on doping (KD). The test-retest correlation and percentage of equally responded queries revealed both questionnaires as reliable. The discriminative validity was proven also since coaches scored better than their athletes on both questionnaires. Athletes declared their coaches as the primary sources of knowledge about nutrition and doping. Among coaches, formal and self-education are equally important sources of information about doping and nutrition. The age is negatively, while the formal education is positively correlated to KD and KSN scores among coaches. Consequently, permanent educational programs about nutrition and doping are emphasized, especially among older coaches and younger athletes.